Optimasi Proses Pembuatan Tepung Pisang Termodifikasi terhadap Kadar Pati Resisten, Nilai Indeks Glikemik, dan Total Kalori Snack Bar - Ihlana Nairfana; Qori'atul Fadilah (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Experimental research in the laboratory was carried out to obtain young kepok banana flour with high resistant starch which was then processed into snack bar products. Young kepok bananas obtained from Sumbawa Regency were treated with different retrogradation treatments, namely: P1 (1 time retrogradation process); P2 (2 times retrogradation process); P3 (3 times retrogradation process); and P4 (4 times the retrogradation process). The research data were analyzed using ANOVA, and each treatment that was significantly different was followed by Duncan's further test at the 5% level of confidence. Both of these analytical methods were processed using SPSS 25 software. The results showed that the retrogradation treatment (autoclaving-cooling) which was carried out repeatedly had a significant effect on increasing the resistant starch content produced in modified banana flour, with a value obtained in treatment P1 = 3.000% , treatment P2 = 4.567%, treatment P3 = 7.333%, and P4 = 11.333%. The P4 treatment was then chosen as a raw material for making snack bars because it has the highest resistant starch content. Testing the value of the glycemic index and total snack bar calories are then calculated. The glycemic index was analyzed through the ratio of area under the curve (area under curve) of food glucose response by measuring fasting blood glucose 0, and once every 30 minutes, namely 30, 60, 90, and 120 minutes after consumption of the test food (modified banana flour snack bar). ) and standard food (glucose water). The results of the Area Under Curve (AUC) for banana flour snack bars were 7.619 and the AUC for glucose was 11.841. The results of the glycemic index value of the modified banana flour snack bar were 42.2. Modified banana flour snack bar in 50 g contains a total of 89.3 Kcal calories.